How do marginalized families engage school choice in inequitable urban landscapes? A critical geographic approach - Yoon, Ee-Seul; Lubienski, Christopher (Education Policy Analysis Archives, 2017)
The normalization of school choice in the education system is purported to provide more schooling options for all families, particularly those who do not have the means to move into affluent areas with ‘better’ schools. Nonetheless, it is still unclear to what extent the policy of school choice has been effective in achieving the goal of providing more choices for marginalized families. This paper aims to fill this gap by examining the K-12 school choice practices and patterns of marginalized urban families, with a focus on their spatial positions and dispositions, in what is arguably one of the most rapidly diversifying and polarizing cities in the world, Vancouver, Canada. An innovative mixed-methods critical geographic approach is used to better understand the families’ school choice participation and related mobility patterns geo-spatially, while exploring their choices phenomenologically.